Classificação do potencial de uso das terras no perímetro urbano de Santa Maria - RS - Pedron, Fabrício de Araújo (2005)
In the last decades, the phenomenon of the urbanization has been transforming a large natural spaces into an extremely altered areas. The conversion of a rural society to an urban one has happened without caring with life quality related to the social and environmental aspects, being the destruction and contamination of the natural resources its consequence, as well as the compromising of areas where the human concentration is increasing. The objectives of this research was to evaluate the land use situation and the urban land use potential of Santa Maria's urban perimeter, through three studies. The first one intended to propose an urban land use potencial system, considering different groups of land use. The second one accomplished the soils survey, determined the land use potential and their current use conflicts in the studied area, while the third study made a spatial analyzes of the land ocuppation and its use conflicts from 1975 to 2002. Tools as remote sensing and digital geoprocessing were used in the research. The results pointed to problems related to land use, where areas are used above its capacity, promoting degradation of the natural resources that might affect the population of the city.